“Draconiano”: a (des)construção de uma identidade em A Elite da tropa 2 - Doroteu, Leandro Rodrigues (2013)
This work applies the theoretical assumptions of French semiotics, postulated by A. J. Greimas, J. Fontanille, to study the simulacrum of posts on the micro-blog Twitter constructed inside the book A Elite da Tropa 2 whose main character responds by the nickname of Dacon1ano - elite cop, retired early by becoming paraplegic. Along the work, reproduces, creating the referential illusion, the whole layout adopted by the micro-blog that has as one of its features set certain writing practices marked by subjectivity, because customarily autobiographical, allowing thus the narrator expresses his feelings and his personal views in posts of up to 140 characters. Based on the semiotic theory, seeks to explain how are composed the subject Dracon1ano, whether in his identity that effectively combated militiaman and that was destructed after an accident, or the identity that which uses the social network to get rebuld, although virtually. Seeks to examine certain passions that born from the struggles of this subject with the other, such as the obstinacy and the resentment. Key-words: French semiotics; identity; A Elite da Tropa 2; Twitter; passions.